Differences in Career Planning for Class XI Students in View of Gender at SMA Negeri 16 Padang - Aini, Syarifah; Putri, Besti Nora Dwi; Putra, Fuaddillah (Holistic Science, 2024)
This research is based on the existence of male students who tend to be more thoughtful in making decisions about career directions and the existence of female students who are still confused in determining career choices. The purpose of this study is to describe: 1) Describe the career planning of students reviewed from the male gender, 2) Describe the career planning of students reviewed from the female gender, 3) Examine the differences in career planning of students reviewed from the male and female gender. This research was conducted using a quantitative method with a comparative type. The population of this study is students in class XI F1 and F2 of SMA N 16 Padang for the 2023/2024 school year totaling 72 students consisting of 51 female students and 21 male students. This sampling technique was carried out with the Total sampling technique, which was as many as 72 students who were the research samples. And the analysis technique used is descriptive techniques and independent samples t test formula with the help of the SPSS for windows application version 20. The results of this study show that the difference in career planning of class XI students reviewed from gender at SMA N 16 Padang can be concluded as follows: 1) the career planning of students reviewed from the male gender is in the high category. 2) Students' career planning is reviewed from the female gender is in the high category. 3) There is a significant difference in the career planning of students from the male and female genders with a coefficient of 0.63 and a significant level of 0.28 Based on the results of this study, it can be concluded that the career planning of female students is higher than that of male students.